2020
DOI: 10.1186/s12910-020-00565-4
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards organ donation in Syria: a cross-sectional study

Abstract: Background The perception of organ donation and brain death among Syrian population has not been previously explored. The goal of this study is to evaluate the attitude and knowledge of organ donation among Syrians and the willingness of this population to donate their organs. Methods We conducted a survey-based cross-sectional study in four hospitals in Aleppo, Syria in November 2019. Patient demographic, awareness of brain death; and attitude tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 24 publications
1
25
1
Order By: Relevance
“…In this study, the general public’s rate of willingness to organ donation was 47.45%. For the domestic public, this rate was similar to the rate in Nanning City (47.92%) [ 18 ], higher than the rate in Ji’nan city (46%) [ 27 ], Zhejiang Province (18.8%) [ 17 ] and Northwest China (29.5%) [ 28 ]; Compared with foreign data, this rate was higher than the rate in Japan (41.9%) [ 29 ], and lower than the rates in Syria (62%) [ 30 ] and in the Middle East (49.8) [ 31 ].…”
Section: Discussionmentioning
confidence: 72%
“…In this study, the general public’s rate of willingness to organ donation was 47.45%. For the domestic public, this rate was similar to the rate in Nanning City (47.92%) [ 18 ], higher than the rate in Ji’nan city (46%) [ 27 ], Zhejiang Province (18.8%) [ 17 ] and Northwest China (29.5%) [ 28 ]; Compared with foreign data, this rate was higher than the rate in Japan (41.9%) [ 29 ], and lower than the rates in Syria (62%) [ 30 ] and in the Middle East (49.8) [ 31 ].…”
Section: Discussionmentioning
confidence: 72%
“… 20 Four recently published empirical studies found that the greater the knowledge of brain death and organ donation, the more families shared a positive impression or attitude toward donation. 31 - 33 , 35 …”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies located focus on brain death and organ donation and, in particular, the public's lack of knowledge surrounding brain death determination when making donation decisions. [31][32][33][34][35] Studies have demonstrated that some people feel that if they agree to organ donation for their loved one, those patients may be diagnosed as dead too soon. 17,52 One study showed that although 80.1% of family members would allow for organ donation after the death of a consenting relative, this rate dropped by 20% when the word death was substituted with brain death, revealing a lack of either understanding or acceptance of the concept and their legal equivalence.…”
Section: Semistructured Interviews 19 Scottish Donor Familiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[31,32] Attitudes toward organ donation Information about the attitudes toward organ donation in the Arab countries is the result of multiple surveys of patients, relatives, professionals, and public members. [33][34][35][36][37][38][39][40][41][42][43][44] According to an extensive multicenter survey in Saudi Arabia, Bahrain, and Egypt by the Renal Transplant Study Group, end-stage renal disease patients tended to take the initiative in seeking living unrelated renal transplantation, despite physician discouragement, and the significant financial burden. [33] A survey of 702 Tunisian physicians, nurses, and technicians by Tebourski et al, 59% were favorable toward organ donation.…”
Section: Bioethical Considerations In Living Organ Donationmentioning
confidence: 99%